Los cuentos de Anancy: huella indeleble de una tradición akán - Pochet Rodríguez, Lina (2013)
The objective of thefollowing paper is to demonstrate how Anancy Stories can be traced back to Africa and identified as such “Nancy Stories” since they present a series of common traits. To do so, the essay approaches the structure of the stories, pointing out the characters, settings, tone, conflicts and themes.